A study on the three-dimensional unsteady state of indoor radon diffusion under different ventilation conditions. (March 2021) - Xie, Dong; Wu, Yangxi; Wang, Chenhua; Yu, Chuck Wah; Tian, Ling; Wang, Hanqing
Highlights: The radon exhalation rate was experimental measured from the concrete material. The 10-h indoor radon accumulated concentration in a sealed room was simulated by CFD. The best air supply ventilation method was determined to reduce indoor radon level. The indoor radon concentration stabilization time under various ventilation modes. The variation of indoor radon concentrations under unsteady-state is described. Abstract: The exhalation of radon from building materials is a serious risk to occupants' health. This paper studied the indoor radon diffusion under three-dimensional unsteady conditions. The radon exhalation rate of building materials was measured using a radon collection chamber combined with a RAD7-based radon/thoron detector. The indoor radon diffusion under different ventilation patterns were simulated by CFD (Computational fluid dynamics) based on the stabilization of radon concentration after 10 h in a closed environment as an initial condition. The results show that the stabilization time is 20 min, which can be reduced by appropriately increasing the air inlet velocity. Further increase in air velocity from 0.3 m s −1 did not produce any significant changes in the stabilization time and the average radon concentration. Our findings show that the better way to reduce indoor radon concentration is to have the air supply inlet at the top or upper side and the air return outlet on the lower side of the room. The indoor radon can be reduced to a steady level after 20 min using the better ventilation method. The findings would contribute to the control of the indoor radon dispersion, and to alleviate and reduce occupants' exposure to high radioactive concentration of radon in urban cities.